Semiconductors (IntechOpen, 2023)
Semiconducting materials are widely used in several applications such as photonics, photovoltaics, electronics, and thermoelectrics, because of their optical and electro-optical features. The fundamental and technological importance of these materials is due to the unique physical and chemical properties. Over the years, numerous methods have been developed for the synthesis of high-efficient semiconductors. Moreover, a variety of approach and characterization methods have been used to study the numerous and fascinating properties of the semiconducting materials. This book collects new developments about semiconductors, from the fundamental issues to their synthesis and applications. Special attention has been devoted to electrochemical growth and characterization.